Metabolic accompaniment of plasma lipoproteins profile in persons with maladaptation - Volodymyr Tsymbryla; Liliya Barylyak; Xawery Żukow; Igor Popovych (Kazimierz Wielki University, 2023)
Background. During the implementation of the project "The relationship between the lipoprotein profile of the blood plasma and the parameters of the neuroendocrine-immune complex, and the influence of the factors of the Truskavets' spa on them", we first divided observed cohort into 5 homogeneous groups that differed from each other by 6 discriminant variables. The purpose of this study is to identify the metabolic accompaniment of plasma lipoprotein profile in the same persons. Material and research methods. The object of observation were 41 volunteers: 20 women aged 30-76 years and 21 men aged 24-69 years without clinical diagnose but with dysfunction of neuroendocrine-immune complex and dysmetabolism. We estimated lipoprotein profile of plasma, determined the levels of the proinflammatory cytokines, parameters of lipid peroxidation as well as routine biochemical and paraclinical parameters. Results. The patients with increased, normal and decreased levels of Dobiásová's&Frohlich's Atherogenic Index of Plasma (D&FAIP) are characterized, together with levels of Triglycerides and HDLP Cholesterol by definition, by specific constellations of levels of IL-6, IL-1, Diene conjugates, Malondialdehyde, Katalase, Glucose, and Alanine aminotransferase (classification accuracy is 98.8%). A close canonical correlation was found between the parameters of the plasma lipoprotein profile, on the one hand, and metabolism and erythroon, on the other (R=0.920). Conclusion. Atherogenic, normal and anti-atherogenic blood plasma is characterized by specific levels of markers of inflammation, lipid peroxidation, cytolysis and erythroon.